1994
DOI: 10.1093/nar/22.8.1346
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-untranslated region of alfalfa mosaic virus RNA 3 contains at least two independent binding sites for viral coat protein

Abstract: The 3'-termini of the three genomic RNAs of alfalfa mosaic virus contain a common sequence of 145 nucleotides (nt) with a specific binding site for coat protein (CP). This sequence consists of several stem/loop structures interspersed with single-stranded AUGC-motifs; in RNA 3 this folding pattern is extended to a region upstream of the homologous sequence. By band-shift assays a minimum of two specific binding sites for CP were identified near the 3'-end of RNA 3. Site 1 consists of the region between nt 11 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
62
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 24 publications
(23 reference statements)
4
62
0
Order By: Relevance
“…2 (b) shows that RNAs with a mutation in AUGC motif 1, 2, 3, 4 or 5 (lanes 3-7) or a mutation in motifs 3 and 5 (lane 8) had template activity similar to that of the wt transcript (lane 2). Previously, we showed that mutations in motifs 2 and 3 affected CP binding to site I in the 3h UTR of RNA3 in vitro whereas mutations in motifs 4 and 5 affected CP binding to site II (Reusken et al, 1994 ;Reusken & Bol, 1996). In addition, we observed that replacing AUGC motif 2 or 3 by AGGC reduced or abolished accumulation of RNA3 in plants, respectively (van der Vossen et al, 1994).…”
Section: M a Van Rossum And Others C M A Van Rossum And Othersmentioning
confidence: 74%
See 4 more Smart Citations
“…2 (b) shows that RNAs with a mutation in AUGC motif 1, 2, 3, 4 or 5 (lanes 3-7) or a mutation in motifs 3 and 5 (lane 8) had template activity similar to that of the wt transcript (lane 2). Previously, we showed that mutations in motifs 2 and 3 affected CP binding to site I in the 3h UTR of RNA3 in vitro whereas mutations in motifs 4 and 5 affected CP binding to site II (Reusken et al, 1994 ;Reusken & Bol, 1996). In addition, we observed that replacing AUGC motif 2 or 3 by AGGC reduced or abolished accumulation of RNA3 in plants, respectively (van der Vossen et al, 1994).…”
Section: M a Van Rossum And Others C M A Van Rossum And Othersmentioning
confidence: 74%
“…The 3h UTRs can be folded into a number of stem-loop structures that are flanked by AUGC motifs and contain specific binding sites for viral CP. Previously, we have shown that the 3h UTR of RNA3 contains a minimum of two independent binding sites for CP, site I being located in the homologous sequence of 145 nt and site II requiring at least part of the region that is unique to the Author for correspondence : John Bol.Fax j31 71 527 4469. e-mail J.BOL!chem.LeidenUniv.nl 3h UTR of RNA3 (Reusken et al, 1994). A CP binding site in the 3h-terminal 39 nt of RNA3 has been analysed in most detail (Houser-Scott et al, 1994Reusken & Bol, 1996).…”
mentioning
confidence: 99%
See 3 more Smart Citations